2020
DOI: 10.22161/ijaers.73.17
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of sisal/ fiberglass reinforced composites

Abstract: The use of plant fibers to replace artificial fibers such as carbon fiber or glass fiber is the subject of studies by many researchers today. Vegetable fibers are considered for their renewability, degradability, low toxicity and low cost. In this work, the mechanical properties of tensile and flexural strength and modulus of elasticity of hybrid composites of sisal fibers with glass fiber in an epoxy polymer matrix were evaluated. The fibers were treated in a 10% by weight sodium hydroxide solution and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…), the final density was 1.46 g cm -3 , and for one produced with polyester, fiberglass and abaca fibers (Musa textilis), the density reached 1.48 g cm -3 . The final density determined in the present work for the composite reinforced with Luffa fibers was lower than the values of 1.30 and 1.21 g cm -3 found by Ferreira et al (2020) for composites produced with epoxy-fiberglass and epoxy-fiberglass-jute fibers (Corchorus capsularis).…”
Section: Discussioncontrasting
confidence: 84%
“…), the final density was 1.46 g cm -3 , and for one produced with polyester, fiberglass and abaca fibers (Musa textilis), the density reached 1.48 g cm -3 . The final density determined in the present work for the composite reinforced with Luffa fibers was lower than the values of 1.30 and 1.21 g cm -3 found by Ferreira et al (2020) for composites produced with epoxy-fiberglass and epoxy-fiberglass-jute fibers (Corchorus capsularis).…”
Section: Discussioncontrasting
confidence: 84%
“…ey concluded that adding more glass fibres into the hybrid composite slightly enhanced the tensile strength with an insignificant effect on tensile modulus. Further studies have observed enhanced tensile, compression, wear resistance, impact, and flexural properties with increasing glass fibre content in the hybrid composites [9,[83][84][85][86][87][88][89][90][91][92].…”
Section: Glass/sisal Fibre Reinforced Polymer Hybrid Compositesmentioning
confidence: 99%
“…Birat et al [86] concluded that the addition of sisal and glass fibres has no significant impact on the crystallization and melting temperatures of the hybrid composites. e study further observed enhanced thermal stability and reduced decomposition rate with the addition of glass fibres.…”
Section: Glass/sisal Fibre Reinforced Polymer Hybrid Compositesmentioning
confidence: 99%
“…On the other hand, in the study reported by [5], the mechanical properties (tensile strength, fexural strength, and modulus of elasticity) of hybrid composites of sisal fbers with glass fber in an epoxy polymer matrix were evaluated. From the results, it has been observed that by mixing sisal and glass fbers, the tensile strength increased by 86% than that of pure sisal and the elastic modulus also increased by 64%.…”
Section: Introductionmentioning
confidence: 99%